Respiratory metabolism: glycolysis, the TCA cycle and mitochondrial electron transport. - Fernie, A; Carrari, F; Sweetlove, L (2004)
The respiratory pathways of glycolysis, the tricarboxylic acid (TCA) cycle and the mitochondrial electron transport chain are ubiquitous throughout nature. They are essential for both energy provision in heterotrophic cells and a wide range of other physiological functions. Although the series of enzymes and proteins that participate in these pathways have long been known, their regulation and control are much less well understood. Further complexity arises due to the extensive interaction among these pathways in particular, and also between cytosolic and mitochondrial metabolism in general. These interactions include those between mitochondrial function in the photosynthetic and photorespiratory processes, amino-acid biosynthesis and the regulation of cellular redox. Recently, a wide range of molecular and biochemical strategies have been adopted to elucidate the functional significance of these interactions.